Evaluation of various methods of point-of-care testing of haemoglobin concentration in blood donors - Singh, Abhay (Blood Transfus, 2015)
BACKGROUND: Point-of-care testing (POCT) devices for determining pre-donation haemoglobin (Hb) concentrations mark the advent of advanced technology for blood banks. POCT devices have undergone several improvements including changes in testing methodology and size of device, befitting the needs of blood donors and blood banks in terms of safety and quality of blood components. This study was planned to evaluate the suitability of non-invasive and invasive POCT devices for blood donor Hb screening. MATERIAL AND METHODS: Pre-donation Hb in apparently healthy blood donors was measured by a non-invasive spectrophotometric based method (NBM-200, OrSense) and an invasive method utilizing reagent free cuvettes (DiaSpect) along with a device using sodium azide-coated cuvettes (HemoControl, EKF diagnostic GmbH). The performance of the devices was evaluated by comparison with the reference method, i.e. an automated cell counter (KX-21). RESULTS: Hb was measured in 485 prospective blood donors. DiaSpect hemoglobin T system was found to be the most sensitive method of POCT for Hb (sensitivity 98.1%) followed by HemoControl (sensitivity 86.8%). NBM-200 was the least sensitive method (sensitivity 71.7%). The intraclass correlation coefficient was highest for DiaSpect (0.78), followed by HemoControl (0.77) and NBM-200 (0.43). The variation of results on repeat testing was high for NBM-200 with a coefficient of variation of 4.28%, compared to 2.19% for DiaSpect. On comparing the mean testing time, DiaSpect (1.9 seconds) was found to be significantly quicker than the other two POCT devices (p<0.001). DISCUSSION: NBM-200 has the apparent advantage of eliminating pain but also a substantial possibility of causing ineligible donors to be accepted. DiaSpect was fast and accurate, with its results showing perfect agreement with those of the standard method. It is, therefore, aptly suited for screening donors in blood banks.